The differential effects of two types of task repetition on the complexity, accuracy, and fluency in computer-mediated L2 written production: a focus on computer anxiety. Issue 5 (3rd July 2016) - Amiryousefi, Mohammad
Abstract : Previous task repetition studies have primarily focused on how task repetition characteristics affect the complexity, accuracy, and fluency in L2 oral production with little attention to L2 written production. The main purpose of the study reported in this paper was to examine the effects of task repetition versus procedural repetition on the complexity, accuracy, and fluency (henceforth CAF) in low–intermediate English as a foreign language (EFL) learners' task-based, computer-mediated L2 written production. A secondary purpose was to examine the relationship between computer anxiety and EFL learners' development of CAF in L2 writing. The study employed a pretest-posttest design with 70 EFL learners from a language learning institution in Iran. The participants were randomly assigned to one of two groups: task repetition or procedural repetition. The task repetition group repeated the same task procedure with the exact same content five times, whereas the procedural repetition group repeated the same task procedure with different content. The participants were also asked to complete the Computer Anxiety Rating Scale to measure their computer anxiety. The results revealed the following: (1) the beneficial effects of both tasks on the participants' L2 written production, (2) the differential effects of task repetition on the participants' writing CAF when compared with procedural repetition, and (3) no statistically significant relationship between computer anxiety and the participants' development of CAF in task-based, computer-mediated L2 written production. Implications are discussed, and avenues for future research are outlined.